Critical Thinking and Epistemic Virtues: The Intersection of Cognition and Character - Gartner, Smiljana; Čop, Tomislav (Od filozofije poučevanja do poučevanja filozofije: Festschrift Rudi Kotnik, 2025)
Originating from a philosophical tradition that dates back to Aristotle, intellectual virtues are part of the rational part of the soul and the methods by which people arrive at the truth. In the process of developing educational documentation, including curricula and learning objectives, the educational system places emphasis on fostering and cultivating intellectual virtues through both teaching and practice. This raises several key questions: which intellectual virtues ought to be prioritised, how they ought to be developed, and what role critical thinking plays in this process. In this chapter, we examine the connection between critical thinking and intellectual virtues: whether critical thinking promotes their development; whether critical thinking is a condition for intellectual virtues, and whether virtues are a condition for the effective use of critical thinking. Based on our analysis, we argue that while critical thinking encompasses multiple elements of epistemic virtue, it cannot be reduced to any single virtue.